Penerapan Model Speak Up Untuk Meningkatkan Aktivtas Dan Keterampilan Berpikir Kritis Siswa Muatan IPS Di Sekolah Dasar - Rizaliannor, Muhammad Abijar; Agusta, Akhmad Riandy (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem contained in this study is the low activity and critical thinking skills of students when learning social studies in elementary schools. The purpose of this research is to describe the quality of learning through teacher activities, analyzing student activities, critical thinking skills and student learning outcomes. The research method used was Classroom Action Research (PTK) which was held in 3 meetings. The subjects of this study were 12 class V students at SDN Terantang 1 2022/2023 academic year. The data collected is qualitative through observation of teacher activities, student activities, and students' critical thinking skills. In addition, quantitative data is obtained through written tests or evaluations to measure student learning outcomes. Data analysis in this study uses descriptive analysis techniques and is presented in the form of tables, graphs and percentage interpretations. The benchmark for research success is that 82% of students exceed the KKM that has been set, namely ≥70. Based on the data and results of this study, it can be concluded that the application of the SPEAK UP (Problem Based Learning, Picture and Picture, Time Token) model can increase students' activity and critical thinking skills.